Measurement Placement Method for Power System State Estimation: Part I - Madtharad C. (2014)
This paper deals with a simple technique for measurement placement method of power system state estimation. The minimum condition number of the measurement matrix is used as the criteria in conjunction with sequential elimination to generalize the measurement placement. The Singular Value Decomposition (SVD) approach will be used to solve the state estimation. The simulation study is performed on the IEEE 14-bus test system by linear weighted least square (WLS). It is found that, this algorithm can give a solution of measurement placement of injection current and voltage that make the power system observable.